The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.2147/jmdh.s341010
|View full text |Cite
|
Sign up to set email alerts
|

Patient Representatives’ Perspectives on Healthcare at the Time of COVID-19 and Suggestions for Care Redesign After the Pandemic: A Qualitative Study in Twenty-Four Countries

Abstract: Objective: Several comments and recommendations called to embed better the patients' and public voice in healthcare policymaking. Still, no studies captured patients' bottom-up perspectives regarding healthcare at the time of COVID-19 at a micro-level in a range of different countries. We, therefore, explored the perspectives of patient representatives in all six World Health Organisation (WHO) regions and extracted suggestions for care redesign after the pandemic. Methods: We conducted semi-structured intervi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Similar findings were observed in another study for challenges with VC in Canada [31]. Patient representatives' perspectives on health care during the pandemic across World Health Organization regions found that telehealth is indispensable in the future but not a solution for everything [32]. Patient representatives were identified as essential connectors and influencers during the pandemic who played an important role in VC implementation.…”
Section: Previous Literaturesupporting
confidence: 80%
“…Similar findings were observed in another study for challenges with VC in Canada [31]. Patient representatives' perspectives on health care during the pandemic across World Health Organization regions found that telehealth is indispensable in the future but not a solution for everything [32]. Patient representatives were identified as essential connectors and influencers during the pandemic who played an important role in VC implementation.…”
Section: Previous Literaturesupporting
confidence: 80%
“…This is needed to make a significant contribution to a successful health system response. This was supported by Stamm et al (2022), who stated that disadvantaged individuals suffered a level of healthcare disparity never seen before because of a lack of technology to implement telemedicine. Coronavirus disease 2019 stigma varies throughout cultures and countries, especially in the African region with some patients rejecting telehealth when offered (Gcabashe & Matambo 2020).…”
Section: Shift From Traditional Chronic Care To Digital Care Servicesmentioning
confidence: 93%
“…Tiotiu et al ( 2021 ) affirm that few practitioners had a systematic strategy and indicated worries about patients who were already poorly controlled, and there was no transition to digital support that could detect and contact high-risk patients for early follow-up. In addition, Stamm et al ( 2022 ) indicate that previous healthcare disparities for underprivileged people worsen during difficult times. Between 5.6% to 14.6% of participants in a study in Asia experienced worsening NCDs and socioeconomic crises along with decreased access to care (Singh, Kaushik & Johnson 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In many countries people have reported reduced access to HIV care during the COVID-19 pandemic [ 22 , 23 ]. HIV care and test facilities were closed down due to healthcare personnel needing to focus on the treatment of patients with COVID-19, making it more difficult for some to access antiretroviral treatment [ 22 , 24 ]. Concerns have also been raised that stigma related to COVID-19 could contribute to layered stigma for people living with HIV [ 23 ].…”
Section: Introductionmentioning
confidence: 99%